Energy Potentials of Briquette Produced from Tannery Solid Waste - Oyelaran, Olatunde Ajani; Sani, Faralu Muhammed; Sanusi, Olawale Monsur; Balogun, Olusegun; Fagbemigun, Adeyinka Okeowo (UI Scholars Hub, 2017)
The vast quantity of waste generated from industries is one of the serious outcomes of unplanned development, resulting into quantum of hazardous organic and inorganic waste generating daily. Proper waste management is a challenging issue that must be addressed adequately. This is, therefore, carried out with a view of assessing the energy and combustion quality of tannery solid waste with a view of converting them into briquettes for cooking, heating and small home industries and reducing the menace caused by tannery waste disposal. The results of the experiments showed that the combustion rate ranged between 0.171 and 0.217 g/min, the boiling time ranged between 27.78 to 34.11 minutes, the ignition time was found between 14.2 to 17.4 minutes. The durability test and humidity resistance test showed that the briquettes have durability ranged between 92.12 and 95.04 while the humidity resistance was between 95.34 and 97.95. The carbon content ranged between 40.79 and 45.15%. Other results showed that the fixed carbon ranged between 89.93 and 95.46%, volatile matter 1.61 to 4.56% and the calorific values were found between 18.03 and 21.86 MJ/kg. The fleshing has better quality than the other three wastes studied.